Uncertainty of fault location prediction due to behavior of simultaneous fault in electrical power system using travelling wave theory - Ngaopitakkul, A.; Apisit, C. (My University, 2011)
This paper presents uncertainty of fault location due to behavior of simultaneous fault in an electrical power transmission system. The fault signal is simulated using PSCAD/EMTDC. The Discrete Wavelet Transform (DWT) is used to detect the high frequency components. The variation of high frequency components of positive sequence current signals at the end of transmission line is considered. The results obtained from the analysis are used in order to locate faults with an application of travelling wave theory. It is found that the travelling wave theory cannot precisely locate simultaneous fault in an electrical power transmission system. © 2011 ISSN 2185-2766.
Keywords: Fault location; Simultaneous fault; Travelling wave; Wavelet transform